FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PRAKTIK KONSUMSI TABLET TAMBAH DARAH (TTD) REMAJA PUTRI DI WILAYAH KERJA PUSKESMAS GILINGAN KOTA SURAKARTA - Devika Rahayuningtyas; Ratih Indraswari; Syamsulhuda Budi Musthofa (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
Adolescents girls’ tend to be riskier of developing anemia than boys because they experience menstruation every month. Based on survey, 4 of 5 students who received blood supplement tablets at school stated that they don’t want to consume it. This research aimed to analyze any factors related to the practice of consuming adolescents girls’ blood supplement tablet in the work area of the Gilingan Health Care Center Surakarta. The method of this research was analytic quantitative with cross sectional design. The population were 542 adolescents girls’ and a sample of 225 adolescents girls’ were selected using simple random sampling. This research used univariate and bivariate analysis (Chi Square). The results of univariate analysis of characteristics respondents were the majority of the respondents were 17 years old (48,0%), education of the respondent’s father is university (56,0%) and also education of the respondent’s mother is university (44,9%), the occupation of respondent’s father is self-employed (30,7%), the occupation of respondent’s mother is housewife (46,2%), with the majority of parents income of Rp. 5.000.000,00 (12,0%). The result of Chi Square test showed that there is a relation between father’s education (p=0,032), parent’s income (p=0,002), attitude (p=0,000), family support (p=0,000), peer support (p=0,000), support from UKS tutor teachers (p=0,001), health workers support (p=0,003), and access to information (p=0,004) with practice of consuming adolescents girls’ blood supplement tablet. Meanwhile, the respondent’s age (p=0,396), father’s occupation (p=1,000), mother’s occupation (p=0,272), mother’s education (p=0,128), knowledge (p=0,850), school support (p=0,210), availability blood supplement tablets in school (p=0,164), and the availability of control cards (p=0,066) had no relation with practice of consuming adolescents girls’ blood supplement tablet.